Kegiatan memanfaatkan lahan pekarangan dengan penanaman bibit pohon sebagai upaya pelestarian lingkungan sehat - Nuryani, Dina Dwi; Triranti, Asih; Mulyanto, Hendra; Indriyani, Jelita Hanan; Inpantri, Karista Putri; Tretilia, Putu Rara; Auliyani, Vievie; Haq, Zam Zam Abdul (JOURNAL of Public Health Concerns, 2025)
Background: The environment is a vital component of human life that must be preserved and maintained sustainably. This situation presents a real challenge that requires the active participation of all levels of society, including higher education institutions, in efforts to address and minimize the impacts. The One Tree One Hope (SPASHA) Program is a form of community service implemented by students from the Community Service Program (KKLPPM) at Malahayati University in Kandang Besi Village, West Kota Agung District, Tanggamus Regency. Purpose: To raise public awareness of environmental conservation, yard utilization, and productive tree planting. Method: Community education through outreach, seedling distribution, planting site determination, and tree planting through mutual cooperation involving the community, village heads, supervising lecturers, and village officials. A total of 100 tree seedlings, consisting of 50 avocado and 50 mixed seedlings (durian, jengkol, and petai) were distributed to eight hamlets. Method: Community education through socialization, seedling distribution, determining planting points, and tree planting through mutual cooperation involving the community, village heads, supervising lecturers, and village officials. A total of 100 tree seedlings, consisting of 50 avocados and 50 mixed seedlings (durian, jengkol, and petai) were distributed to eight hamlets. Results: The activity demonstrated community enthusiasm and active participation, which are indicators of the program's success. In addition to providing ecological benefits such as improved air quality, carbon sequestration, and ecosystem preservation, the program also has the potential to improve community well-being through economically valuable harvests. Conclusion: The One Tree One Hope (SPASHA) movement, a form of community service in environmental conservation, successfully engaged the community actively through outreach, seedling distribution, planting site determination, and tree planting. Community enthusiasm demonstrates that reforestation activities have an impact on a healthy environment and have the potential to provide future economic benefits. Keywords: Environmental health; Land use; Plant conservation; Tree planting Pendahuluan: Lingkungan hidup merupakan komponen penting dalam kehidupan manusia yang harus dijaga kelestariannya dan dilestarikan secara berkesinambungan. Kondisi ini menjadi tantangan nyata yang membutuhkan partisipasi aktif dari seluruh lapisan masyarakat, termasuk lembaga pendidikan tinggi, dalam upaya mengatasi dan meminimalisasi dampak yang ditimbulkan. Program Satu Pohon Satu Harapan (SPASHA) merupakan bentuk implementasi pengabdian kepada masyarakat yang dilaksanakan oleh mahasiswa KKLPPM Universitas Malahayati di Pekon Kandang Besi, Kecamatan Kota Agung Barat, Kabupaten Tanggamus. Tujuan: Untuk meningkatkan kesadaran masyarakat terhadap pelestarian lingkungan, pemanfaatan lahan pekarangan dan penanaman pohon produktif. Metode: Community education melalui sosialisasi, penyerahan bibit, penentuan titik tanam, serta penanaman pohon secara gotong royong dengan melibatkan masyarakat, kepala pekon, dosen pembimbing, dan perangkat desa. Sebanyak 100 bibit pohon, terdiri atas 50 alpukat dan 50 bibit campuran (durian, jengkol, dan petai) didistribusikan ke delapan dusun. Hasil: Kegiatan menunjukkan antusiasme dan partisipasi aktif masyarakat, yang menjadi indikator keberhasilan program. Selain memberikan manfaat ekologis berupa perbaikan kualitas udara, penyerapan karbon, dan pelestarian ekosistem, program ini juga memiliki potensi meningkatkan kesejahteraan masyarakat melalui hasil panen yang bernilai ekonomi. Simpulan: Kegiatan gerakan Satu Pohon Satu Harapan (SPASHA) merupakan bentuk pengabdian masyarakat dalam bidang pelestarian lingkungan, berhasil melibatkan masyarakat secara aktif melalui tahapan sosialisasi, penyerahan bibit, penentuan titik tanam, dan penanaman bibit pohon. Antusiasme masyarakat menunjukkan bahwa kegiatan penghijauan berdampak pada lingkungan sehat dan berpotensi memberikan manfaat ekonomi di masa mendatang.